2016
DOI: 10.1002/ijc.30190
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid and lignan intake and pancreatic cancer risk in the European prospective investigation into cancer and nutrition cohort

Abstract: Despite the potential cancer preventive effects of flavonoids and lignans, their ability to reduce pancreatic cancer risk has not been demonstrated in epidemiological studies. Our aim was to examine the association between dietary intakes of flavonoids and lignans and pancreatic cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. A total of 865 exocrine pancreatic cancer cases occurred after 11.3 years of follow‐up of 477,309 cohort members. Dietary flavonoid and lign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Regarding colorectal cancer (Table 11), it has been demonstrated that flavonoids are able to inhibit the growth of colon cancer cells in vitro [104]. However, in human-based studies, the results are different.…”
Section: Antioxidant Activity Of Dietary Flavonoids and Cancer Incmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding colorectal cancer (Table 11), it has been demonstrated that flavonoids are able to inhibit the growth of colon cancer cells in vitro [104]. However, in human-based studies, the results are different.…”
Section: Antioxidant Activity Of Dietary Flavonoids and Cancer Incmentioning
confidence: 99%
“…However, in human-based studies, the results are different. In a prospective study that examined daily flavonoid intake and its relationship with colorectal cancer, the data showed there was no association between the risk of colorectal cancer and flavonoid intake [104]. Important results were obtained in a study performed by Xu M. et al (2016).…”
Section: Antioxidant Activity Of Dietary Flavonoids and Cancer Incmentioning
confidence: 99%
“…The inverse relationship is attributed to the biological mechanisms related to cell signaling and cell regulation, and is likely due to antioxidant, antimutigentic, and antiproliferative properties associated with nutrients found in fruits in vegetables [43]. Other studies have associated the protective effect with relationship to diallyl disulfide and sulforaphone (present in cruciferous and Allium vegetables) to have the ability to inhibit histone deacetylase (HDACs) enzymes [44,45].…”
Section: Evidence Linking Dietary Intake To the Pathogenesis Of Pamentioning
confidence: 99%
“…This is consistent with the findings in Jiao et al [50] stating that high cooking temperatures is related to increased amounts of N -(carboxymethyl)lysine (CML) advanced glycation end products (CML AGEs). CML AGEs possibly contribute to insulin resistance, oxidative stress, and chronic inflammation [42,43,44,45,46,47,48,49,50,51,52,53]. Moreover, CML AGEs are speculated to contribute to the development of pancreatic cancer by changing the tissue stroma environment [50].…”
Section: Evidence Linking Dietary Intake To the Pathogenesis Of Pamentioning
confidence: 99%
“…Among flavonoids drawing growing scientific attention, there are the flavanones hesperidin (hesperetin-7-O-rutinoside) and its aglycone hesperetin, which are present in high concentrations in citrus fruit and juices, although they can be found in tomatoes and certain aromatic plants, such as mint [ 6 ]. Considering the high intake of citrus fruits and juices worldwide, flavanones significantly contribute to the dietary intake of flavonoids [ 3 , 4 , 7 ]. Hesperidin represents 90% of total flavanones in oranges and orange juices.…”
mentioning
confidence: 99%